Influence of vermicompost and sulphur on growth and yield of garlic (Allium sativum L.) under semi arid climate - B L Yadav, M L Jakhar, S Verma, M R Choudhary, (Journal of Spices and Aromatic Crops, 2013)
A field experiment was conducted during rabi season of 2010–2011 to find out the suitable dose of vermicompost (VC) and sulphur (S) to obtain high yield and net returns in garlic (Allium sativum). Sixteen treatment combinations with four levels of VC (control, 2.5, 5.0 and 7.5 t ha-1) and four levels of S (control, 30, 60 and 90 kg ha-1) were evaluated. Application of 7.5 t ha-1 VC and 90 kg ha-1 S individually produced maximum plant height, number of leaves per plant, chlorophyll content in leaves, fresh weight of leaves, neck thickness, number of cloves per bulb, weight of bulb, bulb diameter and bulb yield, whereas, the combined application of 5.0 t ha-1 VC along with 60 kg ha-1 S was found to be significantly superior with respect to weight of bulb (34.55 g), bulb yield (199.18 q ha-1) and net returns of garlic.